STUDENT SELF-GOVERNMENT AS AN INSTITUTION LEGAL SOCIALIZATION OF SCHOOL CHILDREN - Alokhin Mykhailo М. (Educological discourse, 2015)
In the article reviewed the problem of formation of legal culture of modern Ukrainian youth. The author clarified and analyzed the content and mechanisms of legal socialization of students as one of the ways to overcome legal nihilism and the formation of a legally conscious population. Author systematized types and forms of legal socialization. The article discussed in detail characteristic features, functions and stages of legal socialization of students of secondary schools. Offer both traditional and innovative forms of legal socialization of student youth, predicted the expected results from it for the institution and for society as a whole.